Evaluation of low concentrations of ethanol, butanol, BE, and ABE blended with gasoline in a direct-injection, spark-ignition engine. (1st October 2016) - Fournier, Sébastien; Simon, Guillaume; Seers, Patrice
Abstract: Oxygenated fuel–gasoline blends have been studied intensively in the literature over the years, but few studies have looked at the behavior of oxygenated fuels in combination with a stratified injection strategy in a direct-injection, spark-ignition engine (DISI). This paper presents experimental results obtained using homogeneous and stratified injection strategies with a DISI in which ethanol, butanol, and an acetone–butanol–ethanol (ABE) mixture were blended with gasoline in concentrations of up to 40%. The main findings are that CO emissions were mostly dependent on the equivalence ratio when homogeneous injection was used, resulting in decreasing CO concentrations as the mixture was leaned. On the other hand, stratified injection resulted in increasing CO concentrations when the mixtures were leaned. Unburned-hydrocarbon (HC) emissions were slightly decreased with a homogeneous stoichiometric mixture of ABE blends, while, for the other oxygenates, HC emissions remained constant. With a stratified charge, only E10 decreased HC emissions, while the other blends resulted in increasing HC emissions. Particle emissions first increased with the addition of oxygenates and then decreased for higher blends when homogeneous injection was used. With stratified injection, the particles increased with increasing oxygenate concentration, ethanol having the highest PM emission.